2011
DOI: 10.1370/afm.1172
|View full text |Cite
|
Sign up to set email alerts
|

Impact of EHR-Based Clinical Decision Support on Adherence to Guidelines for Patients on NSAIDs: A Randomized Controlled Trial

Abstract: PURPOSE Electronic health records (EHRs) with clinical decision support hold promise for improving quality of care, but their impact on management of chronic conditions has been mixed. This study examined the impact of EHR-based clinical decision support on adherence to guidelines for reducing gastrointestinal complications in primary care patients on nonsteroidal anti-infl ammatory drugs (NSAIDs). METHODSThis randomized controlled trial was conducted in a national network of primary care offi ces using an EHR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 46 publications
4
44
0
9
Order By: Relevance
“…This finding is consistent with literature on clinical decision support, which shows that clinical decision support in various settings, including primary care, often has only a moderate impact on physician action, 27,28 preventive care testing rates, 2931 adherence to treatment guidelines, 32,33 and meeting quality of care standards. 34 A number of factors may be at play, including the physicians’ workload, perceived inapplicability of the recommendations, inadequate time to document why recommendations were not followed, a lack of training to prepare or prime the end-users, and distraction from the doctor-patient interaction by the electronic reminder.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with literature on clinical decision support, which shows that clinical decision support in various settings, including primary care, often has only a moderate impact on physician action, 27,28 preventive care testing rates, 2931 adherence to treatment guidelines, 32,33 and meeting quality of care standards. 34 A number of factors may be at play, including the physicians’ workload, perceived inapplicability of the recommendations, inadequate time to document why recommendations were not followed, a lack of training to prepare or prime the end-users, and distraction from the doctor-patient interaction by the electronic reminder.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, studies have found that clinicians underuse PPIs for these patients, 15 even when prompted that the patient is at higher risk for gastrointestinal complications. 16 PPIs are also appropriate for long-term maintenance in patients with established GERD and Barrett's esophagus or persistent symptoms (but only at standard doses approved by the FDA or for maintenance in patients with documented hypersecretory states).…”
mentioning
confidence: 99%
“…Few studies outside of those conducted by a small number of leading organizations have demonstrated that typical use of commercially available EHRs in ambulatory settings is associated with improvements in the quality of care, however, and recent research has found that more advanced features of EHRs expected to improve the delivery and quality of care are unevenly available and not widely used. [7][8][9][10][11][12] Additionally, several studies of typical EHR use have found an association with poorer quality of care or no differences when compared with care provided in practices using paper records. [13][14][15] Critics of these studies have noted that cross-sectional or short observational studies are limited and that longer-term users are likely to have learned to more effectively, and successfully, use the technology.…”
Section: Introductionmentioning
confidence: 99%